Conflicting incentives risk analysis: A case study of the normative peer review process - Gaute Wangen (Administrative Sciences, 2015)
This paper presents an approach to conduct risk assessments of complex incentive systems, using a case study of the normative Peer Review Process (PRP). This research centers on appliances and adaptations of the Conflicting Incentives Risk Analysis (CIRA). First as an approach to Root Cause Analysis of a known incident, and then for a full assessment of the incentives in the PRP together with possible risk treatments. CIRA uses an alternative notion of risk, where risk modeling is in terms of conflicting incentives between the risk owner and the stakeholders concerning the execution of actions. Compared to traditional risk assessment approaches, CIRA provides an insight into the underlying incentives behind a risk, and not just the technical vulnerability, likelihood and consequence. The main contributions of this work are an approach to obtain insight into incentives as root causes, and an approach to detecting and analyzing risks from incentives in the normative PRP. This paper also discusses risk treatments in terms of incentives to make the PRP more robust, together with a discussion of how to approach risk analysis of incentives.
Keywords: 350; conflicting incentives risk analysis; human factor; risk management; motivation; decision making; peer review